Phases of athlete development in an age group program - Hogan, P. (American Swimming ASCA Newsletter)
The Mecklenburg Aquatic Club program has been structured on the premise that there are four basic phases of athlete development in age group swimming. At each level of the program, we continually try to evaluate and adapt to the multitude of factors, both scientific and sociological, that impact the growth and development of young athletes. Experience has taught us that the perfect age group program is a moving target that changes as the population we serve changes and as we learn more and more about the development of young people. Following is an outline description of the four phases of development and the basic premises that currently guide our thinking at each of these levels. The final page of this packet is a chart, which provides an overview of the entire MAC program.